METHODS USED TO ESTABLISH THE POSTERIOR PALATAL SEAL FOR MAXILLARY COMPLETE DENTURE PROSTHESIS - Bharat Kumar; Muhammad Rameez; Haroon Rashid (ziauddin University, 2019)
Background: The survey was conducted in Pakistani teaching hospitals to determine techniques and concepts which are used to establish the posterior seal in complete dentures. The aim of this study is to obtain the existing curriculum which is used for teaching the concepts of posterior palatal seal establishment for complete dentures. Methods: A questionnaire was made on online survey development software (Survey Monkey) that consisted of 7 multiple-choice based questions. The questions were related exclusively to the methods for establishing posterior palatal seal for complete denture prosthesis. The forms were forwarded and distributed via e-mail to 75 faculty members of 13 dental Institute of Pakistan who were teaching prosthodontics. A total of 64 faculty members (41 from public sector and 23 from private) responded and participated in the study. Results: Results of our survey indicated that 37.5% of the faculty members were teaching a combination of phonation, nose blowing and fovea palatinae methods. The two vibrating line concept for establishing posterior palatal seal was taught by 64.06% of faculty members, 53.65 % of these place the border of maxillary dentures at the posterior flexion line. Carving the maxillary posterior palatal seal on the master cast was taught by 92.18 % of faculty members. 64% were teaching the post palatal seal carving depth of 0.5-1.5 mm on the maxillary cast, along with consideration of Compressibility of the palatal tissues. The butterfly pattern was the mostly (79.6%) described pattern for carving post palatal seal on the maxillary cast. Conclusion: Statistically there was no significant difference in techniques and concepts which are used to establish the posterior palatal seal, between government and private dental institutes.